(untitled) (Journal of Asian Development Studies, 2014)
Child labor is an important issue now-a-days. The developed and developing countries are taking serious action to eradicate child labor from the society. Asia has a larger number of 18 % children employed as child laborers. A case study of Gujrat, children working as a labor in fan industry, ceramics industry and automobile workshop was taken. Logit, Probit technique is applied in this research. Results conclude that family income and average family size have significant role, negative and positive relation respectively. Father’s education doesn’t have any significant role. The study recommends that the government should introduce income- generating activities for the enhancement of poor people’s income. Population growth needs to be controlled. A campaign should be organized everywhere to make people aware of the adverse effects of child labor. The implementation of labor laws concerning child labor should be taken well care of. Education should be made compulsory and free for all at least up to middle level.